Reorganizing U.S. domestic intelligence : assessing the options - Treverton, Gregory F.; Rand eBooks (Santa Monica, CA : RAND, 2008)
One of the questions in the fight against terrorism is whether the United States needs a dedicated domestic intelligence agency separate from law enforcement, on the model of many comparable democracies. To examine this issue, Congress directed that the Department of Homeland Security perform an independent study on the feasibility of creating a counterterrorism intelligence agency and the department turned to the RAND Corporation for this analysis but asked it specifically not to make a recommendation. This volume lays out the relevant considerations for creating such an agency. It draws on a variety of research methods, including historical and legal analysis; a review of organizational theory; examination of current domestic intelligence efforts, their history, and the public's view of them; examination of the domestic intelligence agencies in six other democracies; and interviews with an expert panel made up of current and former intelligence and law enforcement professionals. The monograph highlights five principal problems that might be seen to afflict current domestic intelligence enterprise; for each, there are several possible solutions, and the creation of a new agency addresses only some of the five problems. The volume discusses how a technique called break-even analysis can be used to evaluate proposals for a new agency in the context of the perceived magnitude of the terrorism threat. It concludes with a discussion of how to address the unanswered questions and lack of information that currently cloud the debate over whether to create a dedicated domestic intelligence agency.
Introduction: Domestic intelligence in context -- Defining domestic intelligence -- Current domestic intelligence arrangements and their performance -- A range of options for improving domestic intelligence -- Assessing structural options -- Weighing pros and cons: An approach for considering the uncertain costs and benefits of organizational change -- Conclusions: The path forward -- Appendixes A: Expert panel participants -- Appendix B: Domestic program map.
"RAND Homeland Security Program and the Intelligence Policy Center."
"RAND Infrastructure, Safety, and Environment."
"This research was conducted jointly under the auspices of the Homeland Security Program within the RAND Infrastructure, Safety, and Environment and the Intelligence Policy Center of the National Security Research Division"--Pg. IV.
Includes bibliographical references (p. 113-125).
Also available on the internet via WWW in PDF format.
Keywords: Intelligence service -- United States; Terrorism -- Government policy -- United States; Terrorism -- United States -- Prevention; Electronic books